A method for measuring coupling coefficients between cores and corrections to mode propagation constants in multicore fibres. (April 2018) - Kalinin, N.A.; Andrianov, A.V.; Kim, A.V.
Abstract: A new experimental method is proposed for reconstructing supermode profiles of a multicore fibre (MCF), small corrections to the propagation constants of its cores and coupling coefficients between the cores without phase-sensitive measurements. The method is based on intensity measurements in the cores at the output of several MCF segments differing in length, using several configurations of controlled light launch into the cores at the fibre input (in the simplest case, by sequentially exciting each core), followed by numerical treatment using an iterative algorithm. The use of the method is demonstrated experimentally for a seven-core fibre. Using numerical simulation, we assess the stability of the method and the effect of the number of measurements on the accuracy of fibre parameter reconstruction.